DEXMEDETOMIDINE COMPARED TO VARIOUS METHODS OF SEDATIVE & ANALGESIC STRATEGY IN INTENSIVE CARE UNITS: A SYSTEMATIC REVIEW AND META-ANALYSIS - JAYAVEL, VIGNESH; SANGEETHA, SRIDEVI; RAMNATH, V; DEVENDIRAN, BALABASKAR (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
Background :Sedation and analgesia are essential for patients in critical care units who are critically ill and receiving mechanical ventilatory support. Sedation analgesia is routinely provided to prevent the pain, reduce their agitation and anxiety, improve the ventilation & synchronization. However, sedation plays a crucial role in critical care units, and the different methods of sedative analgesic therapies help to prevent the undersedation and oversedation. Purpose : The purpose of this review is to assess the effectiveness of dexmedetomidine compared to various sedative and analgesic strategies in decreasing the adverse effects and enhancing patient outcomes in the intensive care units. Materials & Methods: In this study, we conducted a systematic review and meta-analysis to collect relevant evidence for our recommendations and conclusions. We used powerful search engines, including PubMed, science direct, Cochrane Library, and, to gather information from 2014 to 2025. The primary outcome of this study is to identify the effectiveness of sedation and analgesic strategies compared to dexmedetomidine, as well as the duration of mechanical ventilation and length of stay in the intensive care unit. The secondary outcome includes the risk of adverse effects. Results: A total of 18 studies were included in this review, comparing dexmedetomidine with other sedative and analgesic agents such as propofol, midazolam, fentanyl, clonidine, and remifentanil. The majority of studies demonstrated that dexmedetomidine was associated with shorter extubation times and reduced duration of mechanical ventilation compared to traditional sedatives. Several studies also indicated a decrease in ICU length of stay among patients receiving dexmedetomidine. In terms of safety, dexmedetomidine was generally well tolerated, with minimal respiratory depression. However, bradycardia and hypotension were noted as common adverse events, particularly at higher doses or in combination therapies. Comparisons with midazolam and fentanyl showed that dexmedetomidine had a lower incidence of delirium and improved patient-ventilator synchrony. Overall, dexmedetomidine consistently demonstrated favorable outcomes in terms of sedation quality, safety, and recovery compared to other sedative & analgesic strategies in ICU patient populations. Conclusion :Dexmedetomidine offers effective sedation with faster extubation, reduced ICU stay, and minimal respiratory depression. Despite manageable cardiovascular effects, it remains a safe and beneficial option for critically ill patients requiring light, responsive sedation.